The relevance of autotronic engineering competence at vocational high school to the world of work - Yudha Ari Purnama; Wagiran Wagiran (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
This research aims to reveal: (1) the competencies profile of autotronic engineering at vocational high school; (2) the competencies profile of autotronic engineering required by the world of work; and (3) the description of relevance between the competencies profile of autotronic engineering at vocational high school and the competencies profile of autotronic engineering required by the world of work. This research was quantitative research with survey method. This research used descriptive analysis as a data analysis method. The results of this research are as follows. (1) There are 13 competency items in Support of Autotronic System cluster taught at vocational high school and required by the world of work, with a percentage of 81% out of 85% (irrelevant). (2) There are 34 competency items in Engine Management System cluster taught at vocational high school and required by the world of work, with a percentage of 70% out of 67% (relevant). (3) There are 44 competency items in the Chassis Management System cluster taught at vocational high school and required by the world of work, with a percentage of 70% out of 60% (relevant). (4) There are 37 competency items in the Comfort, Safety, and Information Technology cluster taught at vocational high school and required by the world of work, with a percentage of 52% out of 63% (irrelevant). (5) There are four competency items in the Vehicle Control System Cluster taught at vocational high school and required by the world of work, with a percentage of 27% out 59% (irrelevant).